Lyuben Dilov’s Humorous Science Fiction: Literary Historical Contexts - Elena Borisova (International Journal of Slavic Studies, 2021)
The report focuses on satirical prose of Lyuben Dilov as an important part of literaryhistorical processes in Bulgaria between 1960 and 1989. It also traces the development of the science fiction image in literature which uses humor and satire as a key to analyzing the clash between progressive science and backwardness in thinking and living; as a resource of expressing underdeveloped civilization – the inability of people to deal with new technology acceleration and their old understanding of progress. Lyuben Dilov`s prose also uses the unlimited possibilities of science fiction (scientific hypotheses, dreams, etc.) to reveal the metaphorical origins of the genre characteristic of the New Wave in sci-fi, the over-realization of the world in which we live. Turns the science fiction image into tool of social and cultural analysis.